Pregnancy outcomes of 4,200 fetuses with increased nuchal translucency in Henan, China - Guo, Zhenglong; Yang, Wenke; Zhao, Qiongrui; Zhang, Yuwei; Wang, Xin; Wang, Jinming; Wang, Ruili; Hao, Bingtao; Liao, Shixiu (Frontiers in Medicine, 2025)
Background and objectiveIncreased nuchal translucency (NT) thickness measured at 11–14 weeks of gestation in fetuses has been linked to adverse pregnancy outcomes. This study aimed to evaluate pregnancy outcomes in fetuses with NT ≥3.0 mm.MethodsThis retrospective analysis included 4,200 singleton pregnancies diagnosed with increased NT thickness (≥3.0 mm) through first-trimester ultrasound screening across 76 hospitals in Henan Province from 2017 to 2021. Follow-up on pregnancy outcomes was completed through telephone interviews and electronic medical records.ResultsAmong the 4,200 pregnancies with NT ≥3.0 mm, adverse pregnancy outcomes were observed in 31.5% of the fetuses. These outcomes included elective termination of pregnancy (TOP), spontaneous abortion (SA), threatened abortion (TA), and live birth with malformations. A total of 547 fetuses underwent further examination through karyotype analysis after genetic counseling, revealing that 10.2% were aneuploid, primarily due to Trisomy 21 (7.1%).ConclusionThe incidence of increased NT in our study was 0.49%, which was associated with chromosomal abnormalities and developmental disorders, leading to an increased risk of adverse pregnancy outcomes. Abnormal ultrasound soft markers, along with NT > 4 mm, may further elevate the risk of adverse pregnancy outcomes. These findings should be taken seriously in the context of further prenatal diagnosis for fetuses with increased NT.